2021
DOI: 10.3390/s21061948
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Martial Arts Punching Kinematics Using a Vision and Inertial Sensing System

Abstract: Martial arts has many benefits not only in self-defence, but also in improving physical fitness and mental well-being. In our research we focused on analyzing the velocity, impulse, momentum and impact force of the Taekwondo sine-wave punch and reverse-step punch. We evaluated these techniques in comparison with the martial arts styles of Hapkido and Shaolin Wushu and investigated the kinematic properties. We developed a sensing system which is composed of an ICSensor Model 3140 accelerometer attached to a pun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Examples of this include Wilson et al [46], who studied cheetah hunting dynamics, Hayati et al [47], who studied canine gait characteristics, Witte et al [48], who studied the ground reaction force in horses, and Dutto et al [49], who reported ground reaction forces in horses trotting up an incline and on the level over a range of speeds. As aforementioned, we have previously conducted research on the key techniques in the Korean martial art of taekwondo and observed various transitions between different stances and the stance times [17]. An interesting observation that was consistent with previous sports biomechanics and martial arts literature was the notion of a kinetic chain from the ground to the fist.…”
Section: Walking-the-wall Stance Timesupporting
confidence: 76%
See 1 more Smart Citation
“…Examples of this include Wilson et al [46], who studied cheetah hunting dynamics, Hayati et al [47], who studied canine gait characteristics, Witte et al [48], who studied the ground reaction force in horses, and Dutto et al [49], who reported ground reaction forces in horses trotting up an incline and on the level over a range of speeds. As aforementioned, we have previously conducted research on the key techniques in the Korean martial art of taekwondo and observed various transitions between different stances and the stance times [17]. An interesting observation that was consistent with previous sports biomechanics and martial arts literature was the notion of a kinetic chain from the ground to the fist.…”
Section: Walking-the-wall Stance Timesupporting
confidence: 76%
“…The use of trampolining has clear benefits to improving balance, gait, and postural sway as aforementioned. We have also analysed human biomechanics and posture in recent years, as well as the effect of interventions as a means for physical training [17,18]. In addition to these benefits, researchers in more recent years have focused their attempts on forming more direct links between trampolining and its effects on performance in other sports.…”
Section: Benefits and Risks Associated With Trampoliningmentioning
confidence: 99%
“…e storage space and digital signal processing area contain a primary buffer architecture, respectively [5]. Among them, the storage space buffer architecture can quickly store martial arts video.…”
Section: Real-time Target Intelligent Tracking Video Wushu Motion Fee...mentioning
confidence: 99%
“…Among the available technology today, accelerometers can be used to detect punch type and provide data regarding punch force, velocity, power, and other measures that can help quantify punching training structure, volume, and intensity [ 5 , 6 , 7 ]. Other technologies available include high-frame-rate video capture [ 8 ]. Although accelerometers have been tested during punching [ 7 , 9 ], they have primarily included custom-made devices and algorithms that likely are not used by commercial users.…”
Section: Introductionmentioning
confidence: 99%